Gene Expression of SOX2, OCT4, and Nanog by Small Molecule Compound VC6TFZ on Peripheral Blood Mononuclear Cell - Rizka Amalia; Budi Susetyo Pikir; Andrianto Andrianto (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Peripheral blood mononuclear cells are a potential source of cells to be induced into pluripotent stem cells because the collection procedure is easy, minimally invasive, and can be stored in a frozen form. Small molecule compound VC6TFZ consisting of valproic acid (VPA), CHIR990210 (CHIR), 616452, Tranylcypromine, Farsokline, 3-deazaneplanocin (DZnep) and TTNPB has been shown to induce pluripotency in mouse fibroblasts, but this has not been proven in peripheral blood cells. This chemical reprogramming strategy has the potential to be used in producing the desired functional cell types for clinical applications. This study aims to determine whether the small molecule compound VC6TFZ can induce pluripotency of peripheral blood mononuclear cells to become induced pluripotent stem cells. Mononuclear cells were isolated from peripheral venous blood by density gradient centrifugation method. The cells are grouped into 4 groups. Group 1 was the control group, which was not exposed to the small molecule. Groups 2-4 were experimental groups exposed to different doses of the small molecule VC6TFZ. Identification of induced pluripotent stem cells was carried out by identifying colony morphology and pluripotent gene expression of Octamer-binding transcription factor-4 (OCT4), Sex-determining region Y-box 2 (SOX2), and Nanog using Real-Time Reverse Transcriptase-Polymerase Chain Reaction (RT-PCR). Colonies with a round shape, large, cobble stone like, and clear boundaries resembling pluripotent stem cell colonies appeared on the 9th day of the induction process. OCT4 and Nanog gene expression were significantly increased in the treatment group compared to the control.